Cooperative Enhancement of Two‐Photon‐Absorption‐Induced Photoluminescence from a 2D Perovskite‐Microsphere Hybrid Dielectric Structure. (25th April 2018) - Liu, Weiwei; Li, Xiaohong; Song, Yiling; Zhang, Cong; Han, Xiaobo; Long, Hua; Wang, Bing; Wang, Kai; Lu, Peixiang
Abstract: Two‐photon‐absorption‐induced photoluminescence (TPL) from nanostructures is generally inefficient since it is a typical third‐order nonlinear optical process. Herein, a hybrid dielectric structure composed of dielectric microspheres (approximately micrometers in diameter) covering a 2D perovskite flake is reported, which provides a straightforward strategy for enhancing the TPL emission. The microspheres in the hybrid dielectric structure not only concentrate the pumping laser but also effectively increase the detection efficiency of the emitted TPL signal. The internal quantum efficiency of the 2D perovskite is also increased in the hybrid dielectric structure due to a reduced nonradiative rate. These effects cooperatively increase the TPL emission by two orders of magnitude in the hybrid dielectric structure. Moreover, the hybrid dielectric structure is proven to be useful for TPL‐based superresolution imaging at a relatively low excitation power of 0.05 mW. This work demonstrates great promise for developing low‐cost, high‐performance nonlinear nanodevices based on hybrid dielectric structures. Abstract : A hybrid dielectric structure composed of a 2D perovskite flake and dielectric microspheres is used to cooperatively increase two‐photon‐absorption‐induced photoluminescence (TPL) from the 2D perovskite by two orders of magnitude. The hybrid dielectric structure can be utilized for TPL‐based superresolution imaging, requiring significantly less excitation power.